2017
DOI: 10.1038/bjc.2017.45
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoembryonic antigen and cytokeratin-19 fragments for assessment of therapy response in non-small cell lung cancer: a systematic review and meta-analysis

Abstract: Background:This meta-analysis evaluated whether pretherapy serum levels of carcinoembryonic antigen (CEA) and cytokeratin-19 fragments (CYFRA 21-1) are predictive of response to therapy in non-small cell lung cancer (NSCLC) and whether changes in these markers during vs pretherapy are indicative of response.Methods:Original peer-reviewed studies enrolling adults with untreated advanced NSCLC were identified using PubMed. Two reviewers independently extracted data from eligible studies and assessed study hetero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(72 citation statements)
references
References 31 publications
5
64
0
3
Order By: Relevance
“…Moreover, our findings are in agreement with previous clinical studies (Feng et al 2017;Gu et al 2017;Holdenrieder et al 2017;Cedrés et al 2011;Trape et al 2017;Topolcan et al 2007;Antonangelo et al 2015;Sharma et al 2015), and achieved better performance in detecting malignant effusion showing a sensitivity of 98%, a specificity of 95%, and an AUC of 96%. Probably, the low performance of the other studies is due to the low number of MPEs with negative cytology and to the variety of primary tumor sites that they considered (Antonangelo et al 2015;Sharma et al 2015).…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, our findings are in agreement with previous clinical studies (Feng et al 2017;Gu et al 2017;Holdenrieder et al 2017;Cedrés et al 2011;Trape et al 2017;Topolcan et al 2007;Antonangelo et al 2015;Sharma et al 2015), and achieved better performance in detecting malignant effusion showing a sensitivity of 98%, a specificity of 95%, and an AUC of 96%. Probably, the low performance of the other studies is due to the low number of MPEs with negative cytology and to the variety of primary tumor sites that they considered (Antonangelo et al 2015;Sharma et al 2015).…”
Section: Discussionsupporting
confidence: 93%
“…To improve the detection sensitivity in lung adenocarcinoma, we combined Max-IF with serum CEA. The sensitivity of CEA alone as a lung cancer biomarker is very low for lung cancer diagnosis (39). In our study, the sensitivities of CEA (cutoff ¼ 5 ng/mL) in the training set and validation set were 27.3% and 30.7%, respectively.…”
Section: Methylation Pattern Of Histone Gene For Lung Cancer Diagnosimentioning
confidence: 60%
“…Retrospective studies have shown that in patients with NSCLC, particularly those with early-stage disease, elevated levels of the tumor biomarkers, cytokeratin 19 fragment (CYFRA 21-1), and carcinoembryonic antigen (CEA), are associated with a poor prognosis [22][23][24]. A reduction in serum CYFRA 21-1 and CEA levels has also been correlated with response to treatment among patients receiving chemotherapy, although these studies have largely recruited patients with late-stage disease [25][26][27]; these findings were also confirmed in a recent metaanalysis [28]. However, the ability of these biomarkers to predict the outcome of adjuvant CTx in patients with early-stage NSCLC has yet to be determined.…”
Section: Introductionmentioning
confidence: 96%